ANALISIS KARANGAN SISWA PADA MASA DARURAT PENYEBARAN COVID-19 DI KELAS III SEKOLAH DASAR NEGERI 15 PONTIANAK SELATAN - Eva Angelina; Abdussamad Abdussamad; Hery Kresnadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This research was conducted during the Covid-19 emergency. The research was conducted to see the learning process one of the skills in Indonesian language learning, namely writing skills. This study aimed to analyze and describe the quality of students' essays based on series pictures and answer all problems in the study. The method used in this research was descriptive with a qualitative type and a case study form. Sources of research data were the results of essays based on series pictures, students of class III of Public Alementary School 15 South Pontianak, with a total of 22 students. From this research, it can be explained that 7 students' essays that can be analyzed, while 15 students did not get assignments because they were constrained by learning facilities, so they could not collect their essays. The results of the study showed that all student essays had not been written optimally. Of the 7 essays, only 4 students could be categorized as complete in the process because they followed the instructions for the work correctly. Meanwhile, 3 other student essays did not follow the instructions, they did not even finish. With this research, it can describe learning conditions during the Covid-19 emergency. Keywords: Analysis, Essay, Picture Series, Learning during the Covid-19 Emergency, Case Studies.